Studi Pemikiran Ibnu Khaldun Terkait Mekanisme Penetapan Harga Pada Pasar Sentral Soppeng - andi bisyriani (CV. ALIM'SPUBLISHING, 2023)
Abstract. Market transactions work based on the price mechanism. However, overall. The effect of the ups and downs of supply on prices depends on the availability of goods. Prices of goods in the Soppeng central market often change or are unstable, sometimes rising and sometimes falling, these changes are not based on demand or supply factors but depend on situation and condition factors. This research was conducted to find out how Ibn Khaldun's thoughts regarding the price mechanism were realized or not in the Soppeng central market. The type of research used in this study was a qualitative descriptive method. The data in this study were obtained from primary data and secondary data. The data collection techniques used were observation, interviews, and documentation, while the technique used to determine informants was purposive sampling. The data is using description and comparison techniques. The results of this study indicate that: 1). The price mechanism in Ibn Khaldun's thought is influenced by supply and demand, labor value, purchasing power, and the government. 2). In setting prices, traders in the Soppeng central market are based on the quantity of goods demanded by consumers, the price of the goods themselves, transportation costs, the quantity of goods available, prices set by other traders, and according to the ability of the buyer. 3). Ibn Khaldun's thoughts regarding the price mechanism are appropriate or realized in the Soppeng central marke Keywords: Price Mechanism, Ibn Khaldun's Thought.